Quality of life in children with cancer and their normal siblings - Hilda Hilda; Bidasari Lubis; Hakimi Hakimi; Olga Rasiyanti Siregar (Indonesian Pediatric Society, 2015)
Background Cancer treatment in children influences the quality of life of patients and their families. The Pediatric Quality of Life (PedsQL) inventory is a questionnaire to assess quality of life of the healthy and ill children. Objective To compare quality of life in children with cancer and their normal siblings, and to compare quality of life in those with hematologic malignancies to those with solid tumors. Methods A cross-sectional study was conducted among 5-to-18- year-olds at the Hematology-Oncology Division at Haji Adam Malik Hospital, Medan, North Sumatera, from May to July 2012. The case group (subjects with cancer) filled the PedsQL 3.0 and 4.0 questionnaires, while the control group (normal siblings) filled only the PedsQL 4.0 questionnaire. Independent T-test was used to compare the quality of life between children with cancer and their normal siblings. Results There were 46 children in each group. The PedsQL 4.0 results in children with cancer and their normal siblings, and PedsQL 3.0 between hematology malignant and solid cancer were as follows: physical function 36.9 vs. 80.7, respectively (95%CI of differences -52.639 to -34.990; P= 0.0001), emotional function 40.4 vs. 69.3, respectively (95%CI of differences -35.912 to -21.914; P=0.0001), social function 71.5 vs. 93.9, respectively (95%CI of differences - 29.238 to -15.587; P=0.0001), school function 20.7 vs. 74.2, respectively (95%CI of differences - 62.124 to -44.832; P=0.0001), and total score 42.1 vs. 79.3, respectively (95%CI of differences - 43.066 to -31.344; P=0.0001). School function was the most affected parameter in children with cancer compared to their normal siblings. Conclusion There is a significant difference in quality of life between children with cancer and their normal siblings, for all four parameters examined by the PedsQL inventory. However, there are no significant differences in quality of life between children with hematologic malignancy and those with solid cancer.